Mitologia como exposição do absoluto na arte em Schelling - Godoi, Suellen Dantas (2021)
Two decisive purposes guide this research: understanding (i) how and (ii) why Frierdich W. J. Schelling defends mythology as the absolute symbolic exposition (Darstellung), that is, the proper way in which the absolute or God presents itself to the finite human consciousness. Such as stated, the two goals are sometimes get mixed together, but still they are two distinct actions, the effort consists precisely in making them coincide – in identity – in thought. At the same time, we want to emphasize what perhaps is the greatest peculiarity of Schelling’s thought, vital to its understanding, which is the constant recurrence of the duality form, both as a form of presentation of his system and as the proper mode of operation of the rational-reflexive structure of consciousness, which can only be overcome in absolute unity and identity through an aesthetic, and not theoretical- scientific, effort of knowledge. This care will become a resource for the defense of the so controversial unity of Schelling’s thought, to which the present writing shows itself in favor since the first chapter. As a didactic resource, we have also tried to reproduce the form of duality in the methodology, structure, and general organization of the chapters. Since the goal is to make explicit, as the title itself indicates, the definition of mythology as an exposition of the absolute in art, we sought to delineate, inversely, first the scope and role of art, followed by the development of the notion of exposition or hypotyposis to, finally, visualize the concept of mythology as a symbolic absolute exposition already in full operation. Although the attention and focus of the discourse are completely turned to the theme of art and mythology, notwithstanding important concepts to Schelling’s Objective Idealism have not been neglected. On the contrary, notions such as nature, identity, history, consciousness, were included in the argumentative construction of the place of art and mythology in the system. The transformation of the duality figure into a method of organizing the dissertation granted the opportunity and privilege of including a third and final chapter, dedicated to the union of the two antecedents, that is, exclusively to mythology. As it could not be otherwise, its writing does not follow the path of determined knowledge, but of the freedom of imagination that nurtures the aesthetic path. It contains the Schelling’s analysis of the myth of Demeter and Persephone whose divine figure presents itself as an absolute symbol (Sinnbild) of the dissolution of duality into unity and indifference of the opposites.